Inappropriate antibiotic administration in the setting of Charcot arthropathy: A case series and literature review. Issue 1 (February 2022) - Shazadeh Safavi, Kiya; Janney, Cory; Shazadeh Safavi, Pejma; Kunzler, Daniel; Jupiter, Daniel; Panchbhavi, Vinod
Highlights: Acute Charcot neuropathic osteoarthropathy (CN) is often misdiagnosed. Acute CN has similar presentation and etiology to other more common conditions. Early recognition of acute CN ultimately improves patient outcome. Unnecessary antibiotics for CN increase morbidity and antibiotic resistance. Abstract: Aims: Differentiating Charcot neuropathic osteoarthropathy (CN) from infection is challenging. The diagnosis of CN is often missed or delayed, resulting in inappropriate and delayed treatment. We hypothesized that the misdiagnosis of CN results in inappropriate antibiotic prescriptions and explore the sequelae of unnecessary antibiotic use. Methods: A retrospective review of patient electronic medical records from January 2010 to December 2017 was conducted for those diagnosed with CN after being referred to an orthopaedic foot and ankle specialist. Results: Our review showed 58 of 103 (56%) patients received antibiotics on the date, or within the next 7 days, of referral to foot and ankle orthopaedic specialist. The antibiotic of choice given on referral were as follows: Sulfamethoxazole/Trimethoprim 18 of 58 (31%), doxycycline 13 of 58 (22%), clindamycin 13 of 58 (22%), cephalexin 9 of 58 (16%), minocycline 5 of 58 (9%). Conclusion: Missed diagnoses for CN are common and result in complications stemming from inappropriate treatment, delays in appropriate therapy, and may accelerate antibiotic resistance. Misdiagnosis of CN contributes to the inappropriate use of prescription antibiotics.